How do indirect taxes on tobacco products affect inflation? - Cem Çakmaklı; Selva Demiralp; Sevcan Yeşiltaş; Muhammed Ali Yıldırım (Koç University-TÜSİAD Economic Research Forum (ERF), 2018)
This study examines the effects of price adjustments in the tobacco sector on inflation in Turkey. The findings show that the taxes on tobacco products increase inflation in the short-term. However, the effect is rather limited, a 16 basis points increase in inflation if the current 65.25% Special Consumption Tax (SCT) increases by 25 basis points. Factors that cause inflation in the long-run are cost and demand. The cost-driven impact of tobacco prices on inflation is rather limited due to the low weight of this product in the consumption basket. Nevertheless, the structure of the tax multiplier used in tobacco taxation increases cigarette prices in a non-linear fashion and, therefore, has the potential to disrupt inflationary expectations.
Keywords: 330